Influence of Front and Rear Wings on Aerodynamic Forces in a Student Formula Car - Dedy Zulhidayat Noor; Heru Mirmanto; Arino Anzip; Herman Sasongko (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2024)
Aerodynamic forces affect the stability of a car when moving, especially when turning. This study conducted a CFD analysis of the influence of wings on the student formula car when turning. The addition of front and rear wings to the formula car increases drag, downforce, and side forces. Except for an airplane that is landing, large drag forces are always avoided, as well as side forces that can interfere with vehicle stability. Interestingly, in contrast to drag and downforce, the coefficient of side forces tends to decrease as cornering speed increases. The increase in downforce or negative lift in this formula car is more dominant and significant than that in the others, and it is very beneficial in increasing wheel grip and traction on the car’s stability when turning